Further studies with cultures of Shigella classified according to the method used in the USSR - EWING, W. H.; TRABULSI, L. R. (International Journal of Systematic and Evolutionary Microbiology, 1962)
SUMMARY A comparison of the Shigella serotype designations used in much of the literature emanating from the Soviet Union with those employed in the International Shigella Schema is presented for the use of investigators who are interested in the Russian reports on shigellae and bacillary dysentery. Recent literature dealing with such comparative studies is briefly reviewed.